Investigation of Simultaneous Effects of Gyrotactic and Oxytactic Microorganisms on Nanofluid Bio-Thermal Convection in Porous Media - Bubnovich, V (2012)
This paper develops a theory of nanofluid bio-thermal convection in a fluid-saturated porous layer when the suspension contains two different species of motile microorganisms. The goal is to investigate the combined effect of these two species of microorganisms, nanoparticles, and a vertical temperature variation on the hydrodynamic stability of the layer. Since microorganisms are heavier than the base fluid (water) and swim in the upward direction, they act as a destabilizing agency. It is interesting that if one species of microorganisms is present, the system becomes less sensitive to the concentration of the second species, as long as the concentration of the second species of microorganisms remains small. The effect of the nanoparticles depends on whether their distribution is top heavy or bottom heavy. The effect of the temperature variation is destabilizing when heating from the bottom and stabilizing when cooling from the bottom. The utilization of the linear instability theory makes it possible to decouple the effects of these various agencies and obtain an eigenvalue equation that involves four Rayleigh numbers, each characterizing one of the effects described above. © 2012 by Begell House, Inc.